The The Effect of Digital Marketing Strategies, Electronic Word of Mouth (E-Won), and Brand Image on Purchase Intention in Tiktok Shop: The Mediating Role of Customer Trust - Pinto, Leonardo; Rahmawaty, Anisa; Miswanto; Biyanto, Frasto; Siregar, Baldric; Soares, Casimiro (Dinasti Publisher, 2025)
This study aims to examine the influence of Digital Marketing Strategies, Electronic Word of Mouth (E-WOM), and Brand Image on consumer purchase intention in TikTok Shop, with Customer Trust as a mediating variable. The approach used is quantitative with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique. Data was collected through an online questionnaire distributed to 180 respondents who are TikTok Shop users in the Yogyakarta region. The results of the analysis indicate that Brand Image significantly influences Customer Trust and Purchase Intent, and is significantly mediated by Customer Trust. Conversely, Digital Marketing Strategy and E-WOM do not show significant direct or indirect effects on Purchase Intent. Nevertheless, both still contribute to building trust, albeit with relatively small effects. The R-Square values of 0.715 for Customer Trust and 0.791 for Purchase Intent indicate that the model has high predictive power. The Q² test results also support this conclusion, with predictive values above the recommended threshold. This study reinforces the role of Brand Image as a dominant factor in shaping consumer purchase intent, while highlighting the importance of building trust as a key element in digital marketing strategies. The findings also indicate that despite the widespread availability of digital information, consumer purchase intent remains influenced by their perceptions, attitudes, and beliefs, consistent with the Theory of Planned Behavior (TPB) framework used in this study.